Diversity and distribution of Perkinsus spp. along the coast of China: Implications for widespread transmission of Perkinsus spp. in mollusks - Ye, Lingtong; Wu, Lin; Lu, Jie; Yao, Tuo; Wang, Jiangyong; Shi, Shaokun; Yu, Gang; Zhao, Wang (Frontiers in Marine Science, 2022)
Perkinsus species, which are parasitic pathogens of mollusks, have been transmitted and dispersed to various molluscan species along the coastal waters of many countries. However, few studies have addressed the diversity and distribution of Perkinsus spp. along the coast of China. Here we used conventional PCR amplification and sequencing techniques, combined with a qPCR assay as a confirmatory test, to evaluate the prevalence of Perkinsus species in molluscan species among different sea regions of China. Three Perkinsus species—P. olseni, P. beihaiensis, and P. chesapeaki—were detected, with P. chesapeaki reported for the first time along the Chinese coast. Seven of eight molluscan species carried Perkinsus species, including Crassostrea gigas, C. hongkongensis, Sinonovacula constricta, Ruditapes philippinarum, Scapharca subcrenata, Meretrix lyrate, and Haliotis diversicolor. Perkinsus olseni was prominent in the Yellow and Bohai Sea and East China Sea, while P. beihaiensis was prominent in the South China Sea. Most of the molluscan species carried Perkinsus spp. with the medium or low levels of PCR-prevalence (<30%). The three Perkinsus species possess high levels of internal transcriber spacer haplotypes, some of which are shared among many countries. The much higher PCR-prevalence of Perkinsus spp. in the clam Ruditapes philippinarum and the oyster Crassostrea hongkongensis suggests that Perkinsus species may be transmitted and dispersed to other mollusks through the transportation of Perkinsus-carried R. philippinarum and C. hongkongensis. Perkinsus carrying tended to be generally linked with a broader geographic range, lower prevalence, more diversified molluscan hosts, and more diversified Perkinsus haplotypes.